Telo kot kulturna vrednota - Tihanov, Galin (Slavistična revija, 2001)
In this article I explore the dynamic of Bakhtin's idea of the human body as a cultural value from the early essay 'Author and Hero in Aesthetic Activity' to his 1965 vook Rabelais and His World. I also outline some of the most relevant sources of Bakhtin's interest in this problem and reflect on how Bakhtin's treatment of it bore on the idea of history in his writings.
Keywords: aesthetics; Bahtin, Mihail Mihajlovič, 1895-1975; body; history